2019
DOI: 10.3847/1538-3881/ab1097
|View full text |Cite
|
Sign up to set email alerts
|

Stellar Occultation by Comet 67P/Churyumov–Gerasimenko Observed with Rosetta's Alice Far-ultraviolet Spectrograph

Abstract: Following our previous detection of ubiquitous H 2 O and O 2 absorption against the far-UV continuum of stars located near the nucleus of Comet 67P/Churyumov-Gerasimenko, we present a serendipitously observed stellar occultation that occurred on 2015 September 13, approximately one month after the comet's perihelion passage. The occultation appears in two consecutive 10-minute spectral images obtained by Alice, Rosetta's ultraviolet (700-2100 Å) spectrograph, both of which show H 2 O absorption with column den… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
3
8
0
Order By: Relevance
“…The bottom panel of Figure 1 shows an estimate of the H 2 O column density for the extracted rows in each Alice exposure using a slightly modified version of the empirical coma model of Hansen et al (2016). We showed in Keeney et al (2019) that the column density of water, N H2O , measured by Alice in absorption against the continuum of UV-bright stars passing near the nucleus of 67P/C-G is consistent with the predictions of the Hansen et al (2016) model; however, we noted that our measurements disagreed with their prediction very close to perihelion where their parameterization of the H 2 O production rate, Q H2O , is discontinuous. Here we remove this discontinuity by adopting the Hansen et al (2016) parameterization of Q H2O before perihelion and after solstice, and linearly interpolating in-between.…”
Section: Creation Of Grand Sumsupporting
confidence: 73%
See 1 more Smart Citation
“…The bottom panel of Figure 1 shows an estimate of the H 2 O column density for the extracted rows in each Alice exposure using a slightly modified version of the empirical coma model of Hansen et al (2016). We showed in Keeney et al (2019) that the column density of water, N H2O , measured by Alice in absorption against the continuum of UV-bright stars passing near the nucleus of 67P/C-G is consistent with the predictions of the Hansen et al (2016) model; however, we noted that our measurements disagreed with their prediction very close to perihelion where their parameterization of the H 2 O production rate, Q H2O , is discontinuous. Here we remove this discontinuity by adopting the Hansen et al (2016) parameterization of Q H2O before perihelion and after solstice, and linearly interpolating in-between.…”
Section: Creation Of Grand Sumsupporting
confidence: 73%
“…However, the line of sight experiencing this absorption (Sun to comet, then comet to Rosetta) differs from the line of sight seen by Alice. Thus, we adopt the N H2O predictions of the modified Hansen et al (2016) model described in Section 3 for the Alice line of sight, which Keeney et al (2019) showed are consistent with Alice absorption measurements against the continuum of background stars, rather than the values produced as part of the spectral fitting.…”
Section: Fitting and Removal Of Detected Speciesmentioning
confidence: 99%
“…Analysis of Alice remote sensing UV data yielded much higher O 2 abundances relative to water (Keeney et al 2017) than the ROSINA/DFMS analysis ), up to 60% O 2 /H 2 O. A more recent analysis of Alice stellar occultation data conversely yielded O 2 /H 2 O abundances comparable to those measured by ROSINA (Keeney et al 2019). The source of these differences is not understood yet, although high-energy electron impact not accounted for in the original analyses has been suggested.…”
Section: Other Volatilesmentioning
confidence: 86%
“…Whether this O 2 would be detected by DFMS is uncertain as the DFMS response under exposure to a lowpressure water plasma containing O 2 is unknown (Yao and Giapis 2018). It is also important to note that Alice has detected O 2 independently of ROSINA (Keeney et al 2017a), and post-perihelion Alice results indicate that the relative O 2 /H 2 O decreases with increasing impact parameter above the nucleus (Keeney et al 2017b). Although the Alice measurements may arguably be affected by spacecraft-produced O 2 , the observed O 2 /H 2 O variation with impact parameter would be unlikely within this framework.…”
Section: Omentioning
confidence: 99%